Analisis Spasial Temporal Klorofil-a Perairan Ponelo Kepulauan Provinsi Gorontalo Tahun 2018-2022 Menggunakan Data Landsat 8 - Romansah Wumu; Nia Kurniadin; Shabri Indra Suryalfihra (Politeknik Pertanian Negeri Samarinda, 2023)
Indonesia's maritime area covers approximately 3.25 million km2, which means that 70% of Indonesia's total area is comprised of the ocean. This indicates the enormous potential that Indonesia's ocean holds. The ocean is a crucial resource for the Ponelo Islands community, whose main livelihood is fishing. The marine ecosystem is vulnerable to environmental changes and pollution. Chlorophyll-a can serve as an indicator of the health of marine waters. Mapping the distribution of chlorophyll-a on the ocean's surface can be achieved through remote sensing technology. The study utilized the Nuriya Algorithm (2010) to derive the chlorophyll-a content in surface waters using Landsat-8 data from 2018-2021. Data processing is done through Google Earth Engine (GEE) which has the ability to process large amounts of data quickly (Big Data). The findings indicate an increase in chlorophyll-a content in the waters of Ponelo Islands at the beginning (DOY 0-20) and end (DOY 300-325) of the year. On a spatial scale, the average chlorophyll-a is widely distributed in the waters of Ponelo but is more concentrated in the coastal areas. This indicates that coastal areas of the Ponelo Islands may be more vulnerable to pollution and environmental changes and require special attention in environmental management and marine ecosystem conservation efforts.